Beatmung von Neugeborenen und Säuglingen - Berger, T. M. (Anaesthesist, 2004)
Anaesthesiologists must be familiar with the particularities of the respiratory physiology of newborns and infants when providing perioperative care to these patients. Even brief periods of inadequate respiratory support can cause atelectatrauma and volutrauma which in turn can have deleterious cardiorespiratory consequences and accentuate pre-existing lung disease. A variety of respirators and respiratory support strategies are available and should be selected to meet a patient’s particular needs. Optimal PEEP and normal tidal volumes during conventional ventilation, high volume strategy during high frequency ventilation, and permissive hypercapnia are the corner stones of a lung protective strategy. Using an interdisciplinary approach, surgery in the intensive care unit using total intravenous anaesthesia with the uninterrupted use of the ICU equipment is an attractive option for the most vulnerable patients in this age group.